Integrated product design, shelf-space allocation and transportation decisions in green supply chains. Issue 19 (2nd October 2019) - Kuiti, Mithu Rani; Ghosh, Debabrata; Gouda, Sirish; Swami, Sanjeev; Shankar, Ravi
Abstract : In this paper, we examine a supply chain consisting of a manufacturer and retailer where the manufacturer undertakes greening efforts in terms of pack-size reduction and transportation cost reduction. The retailer decides on shelf-space allocation for the product. Both the players benefit from the greening efforts of the manufacturer. In such a setting, we examine strategic decisions of the players and compare and contrast the performance of the decentralised supply chain with the centralised supply chain. We also examine the effect of collaborative mechanisms by modelling two contracts in which the retailer offers a transportation cost reduction effort based contract and a two-part tariff contract. We find that the decentralised supply chain leads to lower greening efforts and shelf-space allocation decisions. We also find that the contracts improve pack-size reduction effort, transportation cost reduction effort and shelf-space allocation, while also improving the profitability of individual players. The findings demonstrate a scope for supply chain collaboration between manufacturer–retailer pairs in this setting. The paper uniquely combines three critical elements in supply chains, namely, product design, transportation and retailing decisions, and aims to provide insights into the decision making of players considering environmental waste and pollution. The paper also reflects consumer behavior and trade-offs that the supply chain players face.